RCNT2 extracellular cysteines, Cys615 and Cys649, are important for maturation and sorting to the plasma membrane. Issue 23 (12th October 2014) - Pinilla-Macua, Itziar; Claudio-Montero, Ana; Pastor-Anglada, Marçal
Abstract : rCNT2 is a purine‐preferring concentrative nucleoside transporter implicated in the regulation of extracellular adenosine levels and purinergic signaling. This study addressed the analysis of the CNT2 C‐terminus tail as a domain likely to be implicated in transporter sorting. The topological mapping of this segment revealed that Cys 615 and Cys 649 are important residues for the proper trafficking of CNT2 to the plasma membrane. The inhibition of protein disulfide isomerase (PDI) and ER glycosidase I and II impaired rCNT2 trafficking to the cell surface, similarly to Cys 615 and Cys 649 mutants. The present work suggests these two cysteine residues are relevant for the proper sorting of the transporter and its functional performance. Abstract : Partial deletions in rCNT2 C‐terminal tail showed coordination between two segments. rCNT2 needs to be oxidized to traffic to the plasma membrane. C615 and C649 are relevant for rCNT2 sorting to the plasma membrane. Inhibition of ER‐maturation results in similar trafficking impairment as Cys mutants.